OPTIMIZATION OF MANAGEMENT INFORMATION SYSTEMS IN IMPROVING ACCURACY AND EFFICIENCY OF ACCOUNTING REPORTING: LITERATURE STUDY AND IMPLEMENTATION ANALYSIS - Abigail Claudya Sesa; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the role of Management Information Systems (MIS) in accounting reporting in the public and private sectors. Through a literature review and a descriptive qualitative approach, it was found that the implementation of MIS significantly contributes to the efficiency, accuracy, and speed of the financial reporting process. This study highlights implementation challenges and system optimization strategies to support better decision-making.